Analysis of Characteristics of Toddlers, Mothers, and Living Environment on the Incidence of Diarrhea in Toddlers in Samarinda City in 2024 - Nadila Lupita Puteri; Oktia Woro Kasmini Handayani; Yuni Wijayanti (Universitas Negeri Semarang, 2024)
Diarrhea is still a challenging health problem for children under five years of age in Indonesia. Diarrhea due to waterborne diseases is still prevalent in Samarinda, and this environmental health problem could trigger outbreaks in multiple regions. The objective of this study was to analyze the effect of child characteristics, mother characteristics, and environmental characteristics in Samarinda. The research method used a case-control design with a sample of 124 (62 cases and 62 controls), and the data was obtained by interview using a questionnaire. The sampling technique was consecutive sampling. Data analysis was carried out, including univariate and bivariate, by chi-square statistical tests. And multivariate analysis by multiple logistic regression. The results showed that the incidence of diarrhea with nutritional status P = 0.027 (OR = 2.292; 95% CI: 1.092-4.807); history of exclusive breast-feeding P = 0.040 (OR = 2.180; 95% CI: 1.030-4.612); history of immunization status P = 0.014 (OR = 2.860; 95% CI: 1.218-6.716); worker mother P = 0.08 (OR = 0.354; 95% CI: 0.163-0.771); and clean water source P = 0.09 (OR = 2.754; 95% CI: 1.280-5.923); and drinking water management P = 0.017 (OR = 2.444, 95% CI: 1.166-5.127). The factors that did not relate significantly in this research were the child’s age (P = 0.402), mother’s age (P = 0.467), mother’s education (P = 0.534), and family income (P = 0.579). The result from the multivariate shows the variable that had the most significant association with diarrhea was the mother’s occupation. The accessibility to clean water sources was an intervening variable that played an important role in diarrhea cases in Samarinda. Health institutions also need to conduct periodic water quality checks and increase community knowledge about water quality and diarrhea prevention. This study could provide valuable input for diarrhea prevention and control programs.